The Effect of Red and Blue on Gross and Fine Motor Tasks: Confirming the Inverted-U Hypothesis - Hong, Xiaobin; Xu, Aiai; Shi, Yan; Geng, Lu; Zou, Rong; Guo, Yuanbing (Frontiers in Psychology, 2022)
Previous studies have shown that the color red can affect basic motor functioning (Elliot and Arts, 2011; Payen et al., 2011). However, these studies utilized simple gross motor tasks rather than those assessing complex fine motor skills. Moreover, these empirical studies were theoretically based on the threat–behavior link in human and non-human animals, and neglected the relationship between arousal and motor performance. According to the Yerkes–Dodson law and the inverted-U hypothesis in sport psychology, for simple motor tasks, high arousal (associated with the color red) is more advantageous than low arousal (associated with the color blue); for complex motor tasks, low arousal (blue color) is more advantageous than high arousal (red color). The current research examined the effect of color on different kinds of motor skills (fine motor and gross motor) based on the inverted U-hypothesis. In Experiment 1, we examined the effect of red and blue on dart-throwing performance, whereas in Experiment 2, we examined the effect of red and blue on grip strength performance. The results showed that blue enhanced performance on dart-throwing (Experiment 1) and red enhanced performance on handgrip force (Experiment 2). These results indicate that the type of motor skill assessed moderates the influence of red and blue on motor performance.